1984
DOI: 10.1063/1.446839
|View full text |Cite
|
Sign up to set email alerts
|

An ion beam study of reactive scattering of halide ions by methyl halides

Abstract: Measurements of electron detachment cross sections, reactive charge transfer, and differential elastic and inelastic scattering cross sections for Cl−, Br−, and I− ions on CH3I, CH3Br, and CH3Cl targets are reported. The energy range for the experiments is from 3 to 150 eV. Of the very large number of reaction channels open, it appears that most make significant contributions to the total cross section for sufficiently high projectile energies. The SN2 reaction, which may be dominant at lower energies, was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Such high internal excitation is close to the dissociation limit of CH 3 Cl, which supports the conclusion that the decline in the total cross section for reaction 2 above 4 eV is due to competitive dissociation channels. The high internal excitation of CH 3 Cl also absorbs energy that might otherwise cause collisional electron detachment, which was observed 89 only above 6 eV.…”
Section: Product Velocity Distribution Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high internal excitation is close to the dissociation limit of CH 3 Cl, which supports the conclusion that the decline in the total cross section for reaction 2 above 4 eV is due to competitive dissociation channels. The high internal excitation of CH 3 Cl also absorbs energy that might otherwise cause collisional electron detachment, which was observed 89 only above 6 eV.…”
Section: Product Velocity Distribution Results and Discussionmentioning
confidence: 99%
“…In ion beam/gas cell experiments on Cl -+ CH 3 Br, White et al 89 reported that electron detachment cross sections, Cl + e -+ [CH 3 Br], rise from an apparent threshold at 6 eV (well above the thermodynamic detachment threshold of EA(Cl) 72 ) 3.6 eV) to a plateau of 10 × 10 -16 cm 2 above 100 eV (c.m.). That indicates that the electron detachment process is an additional competitive channel leading to the decline of reactions 2 and 3 above 6 eV.…”
Section: Sn2 and Bromine Abstraction Reactionsmentioning
confidence: 99%
“…In order to ensure that there were no undesired ions in the primary ion beam, the apparatus described in Refs. [21][22][23][24] was improved to incorporate a 90° double focusing sector magnet, with a resolving power of approximately 100. The 0-and OH-mass peaks were clearly resolved; the observed contamination of the 0-primary ion beam by OH-was less than 1 %.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Guided ion beam methods allow studies at low collision energies under single-collision conditions with sensitive detection of products. The SIFT/drift results of Bierbaum and co-workers represent the only definitive previous observation of reaction 3. , In a scattering study of Cl - + CH 3 Cl at relative energies greater than 3 eV, collisional electron detachment but no S N 2 products were observed . Reaction 1 for endothermic systems, with X = Cl, Br, or I and Y = H or F, has been studied in beam/gas experiments, but the observation of true S N 2 products was uncertain because the threshold energies were high enough for dissociative processes to be responsible (e.g., formation of Y - + CH 3 + X).…”
Section: Introductionmentioning
confidence: 99%
“…5,7 In a scattering study of Cl -+ CH 3 Cl at relative energies greater than 3 eV, collisional electron detachment but no S N 2 products were observed. 31 Reaction 1 for endothermic systems, with X ) Cl, Br, or I and Y ) H or F, has been studied in beam/gas experiments, 32 but the observation of true S N 2 products was uncertain because the threshold energies were high enough for dissociative processes to be responsible (e.g., formation of Y -+ CH 3 + X). We also examine reaction 4 to investigate kinetic isotope effects.…”
Section: Introductionmentioning
confidence: 99%